Erastin Reverses ABCB1-Mediated Docetaxel Resistance in Ovarian Cancer - Zhou, Hai-Hong; Chen, Xu; Cai, Lu-Ya; Nan, Xing-Wei; Chen, Jia-Hua; Chen, Xiu-Xiu; Yang, Yang; Xing, Zi-Hao; Wei, Meng-Ning; Li, Yao; Wang, Sheng-Te; Liu, Kun; et al. (Frontiers in Oncology, 2019)
Overexpression of drug efflux transport ABCB1 is correlated with multidrug resistance (MDR) among cancer cells. Upregulation of ABCB1 accounts for the recurrence of resistance to docetaxel therapy in ovarian cancer with poor survival. Erastin is a novel and specific small molecule that targets SLC7A11 to induce ferroptosis. In the present research, we explored the synergistic effect of erastin and docetaxel in ovarian cancer. We confirmed that the co-delivery of erastin with docetaxel significantly decreased cell viability, promoted cell apoptosis, and induced cell cycle arrest at G2/M in ovarian cancer cells with ABCB1 overexpression. Mechanistically, erastin dominantly elevated the intracellular ABCB1 substrate levels by restricting the drug-efflux activity of ABCB1 without alteration of the expression of ABCB1. Consequently, erastin can reverse ABCB1-mediated docetaxel resistance in ovarian cancer, revealing that the combination of erastin and docetaxel may potentially offer an effective administration for chemo-resistant patients suffering from ovarian cancers.